O semanário Bundas e o jornalismo econômico - Taveira, Caroline Gonçalves [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This dissertation analyzes the ways of exercising economic journalism, aiming to show how this can become understandable to any readership. Throughout the chapters, among theories and analyzes, seek denote as the alternative media can help facilitate economic understanding information and leave it to the understanding not only of people involved in the economic universe, as well as those readers who are unfamiliar with the jargon economic journalism. By the above, we have seen in the weekly Bundas, considered alternate periodic and circulated in the late 1990s, a medium that facilitated the reading of the texts on economics. Starding from a textual study, inspired by the Content Analysis Bardin, the aim of the paper is to show that it is possible to perform the practice of economic journalism under the alternative point of view, showing that these can bring information to the public in a much more attractive way player and understandable than the big print media

Esta dissertação procura analisar as formas de exercício do jornalismo econômico, com o objetivo de mostrar como este pode se tornar compreensível a qualquer público leitor. Ao longo dos capítulos, dentre teorias e análises, buscamos denotar como a imprensa alternativa pode contribuir para facilitar a compreensão da informação econômica e deixá-la ao entendimento não só de pessoas envolvidas no universo econômico, como também àqueles leitores que não estão familiarizados com os jargões do jornalismo econômico. Mediante ao exposto, vimos no semanário Bundas, periódico considerado alternativo e que circulou no final dos anos de 1990, um meio que facilitou a leitura dos textos sobre economia. Partindo de um estudo textual, inspirado na Análise de Conteúdo de Bardin, o intuito do trabalho é mostrar que é possível realizar a prática do jornalismo econômico sob o ponto de vista alternativo, evidenciando que esses podem levar informação ao público leitor de maneira muito mais atrativa e compreensível do que os grandes veículos impressos
Keywords: Imprensa alternativa - Humor, satira, etc; Jornalismo; Economia; Underground press publications - Facetial, satire, etc